Deep and crustal factors of thorium-uranium mineralization of the Golovanevskaya zone of Ukrainian Shield - М. О. Ярощук; О. В. Вайло; А. Є. Ганевич (Геофизический журнал, 2021)
The article discusses the features of the deep and crustal structure of the Golovanevskaya zone, the geochronological sequence of the main stages of its formation. The characteristic of thorium-uranium ore occurrences and deposits is given; and the main stages of their formation. The stages of successive concentrations of uranium and thorium in connection with the processes of sedimentation, volcanism, metamorphism, ultrametamorphism, and tectonic-magmatic activation are determined.